Evaluation of febrile neutropenic attacks in a tertiary care medical center in Turkey - Suzan Sacar; Sibel Kabukcu Hacioglu; Ali Keskin; Huseyin Turgut (Journal of Infection in Developing Countries)
Background: Infectious complications in febrile neutropenic patients are still major causes of morbidity and mortality despite significant advances in diagnostic techniques and antimicrobial therapy. In this study, we describe the characteristics of patients with hematological malignancies who were evaluated for suspected infection. This study was also conducted to assess the isolation rate of bacterial and fungal causative agents in febrile neutropenic attacks. Method: The study was conducted at Pamukkale University Hospital, Turkey. In order to identify the characteristics of patients with hematological malignancies in the presence/suspicion of any accompanying infectious disease, patients’ charts with hematological malignancies were reviewed for signs/symptoms of any infection between October 1, 2001, and May 31, 2005, retrospectively. Results: Overall, 90 infectious episodes occurred in 59 patients. The most common underlying diseases were acute myelogenous leukemia (61.0%) and acute lymphocytic leukemia (15.3%). The absolute neutrophil count was lower than 100/mm³ in 33 (36.7%) episodes. Microbiologically and clinically documented infections and fever of unknown origin were observed in 35.6%, 28.9%, and 35.6% of the participants, respectively. Bloodstream infections and pneumonia were detected in 21.1% and 18.9% of episodes, respectively. Gram negative organisms were most common (58.4%), followed by gram positive cocci. A combination of third generation cephalosporin and an aminoglycoside were used in 44.4% of episodes initially. Fever resolved in 24.4% of episodes using the initial therapy. The mortality rate was 15.6%. Conclusion: These results showed that infections with gram-negative bacteria continue to predominate in febrile neutopenic episodes in our center.